Meshed Architecture of Performance as a Model of Situated Cognition - Gallagher, Shaun; Varga, Somogy (Frontiers in Psychology, 2020)
In this paper we engage in a reciprocal analysis of situated cognition and the notion of ‘meshed architecture’ as found in performance studies (Christensen, Sutton & McIlwain 2016). We argue that the model of meshed architecture can operate as a tool that enables us to better understand the notion of situated cognition. Reciprocally, by means of this new understanding of situation we develop a richer conception of meshed architecture. This enriched notion of a meshed architecture includes affect and bottom-up, non-automatic, intrinsic control aspects of body-schematic processes and intelligent habits, on a vertical axis, as well as extended, ecological and worldly (material, normative, social, cultural) constraints and affordances on a horizontal axis. This gives us a very productive way to think about how various elements come together in skilled action and performance, but also a detailed way to characterize situated cognition.